The Legislative Approach and System Improvement of China’s Compulsory Licensing for Drug Patents - Cao Z; Chen Y; Jiang W; Li W (Dove Medical Press, 2021)
Zhang Cao,1 Yichao Chen,2 Wenjie Jiang,1 Wei Li3 1School of Law, Zhejiang University of Finance and Economics, Hangzhou, Zhejiang Province, People's Republic of China; 2School of Law, Jinan University, Guangzhou, Guangdong Province, People's Republic of China; 3Intellectual Property Institute, Jinan University, Guangzhou, Guangdong Province, People's Republic of ChinaCorrespondence: Wei Li Email iprecht@126.comAbstract: Compulsory licensing for drug patents is of great significance to ensure the accessibility of drugs. Although the development of China's compulsory licensing system for drug patents has been gradually improved, there are still problems. For example, the scope of the object is not realistic, the setting of the initiating subject is unreasonable, the reasons for issuance are not clear, the duration and scope of the license are not refined, and the provisions on the exploitation fee are missing. Consequently, in order to improve China's compulsory licensing system for drug patents, it is necessary to expand reasonably the scope of the object, remove the restrictions on the initiating subject, adjust the initiating rights of different subjects, determine the duration and scope of the license and the applicability of the hearing on a case-by-case basis, and determine a reasonable exploitation fee by taking into account the national income, patent cost, market share and other factors, in consideration of the flexibly international norms and the actual situation in China.Keywords: drug patents, compulsory licensing, public health